EFFECTIVENESS OF COMBINATION OF FEED FORM CAKE AND FEED NATURAL SILK WORMS (TUBIFEX SP) ON FEED CONVERSION RATIO (FCR), SPECIFIC GROWTH RATE AND GIANT FRESHWATER PRAWN SURVIVAL (MACROBACIUM ROSENBERGII) LARVAL STAGE - Sutarjo, Ganjar Adhywirawan (University of Muhammadiyah Malang)
This study aimed to determine the effectiveness of the combination of cake feed and silk worm feed on feed coneration ratio (FCR), Survival, and specific growth rate (SGR) of prawn larvae (Macrobacium rosenbergii). The research was conducted on 8 February - 9 March 2018 at the Fisheries Laboratory of University of Muhammadiyah Malang. Shrimp used in this study is larval prawns stadia larvae. This research was conducted by experimental method using randomized block design (RAL) with 5 treatments and 4 replications. P1 100% silk worm and 0% cake feed, P2 25% silk worm and 75% cake form feed, P3 50% silk worm and 50% cake form feed, P4 75% silk worm and 25% cake feed, P5 100 % feed cake form. Feed is given in ad-station for 40 days. Observed data include Feed coneration ratio (FCR), Survival, specific growth rate (SGR), and water quality. The results showed that the combination of cake feed and silk worm feed had a significant effect on the growth rate of Specific (SGR) Fcount 7.58> from F. Table 5% (3.06) 1% (4.89), While no effect For Figures F count 0.90 <of F. Table 5% (3.06) 1% (4.89) and Feed Converation Ratio as F count 2.23 <of F. Table 5% (3.06) 1 % (4.89). Water quality on maintenance media against a reasonable range for shrimp cultivation. Keywords: fish cake, silk worm, giant freshwater prawn, growth